Speak Chinese today a basic course in the modern language - Beverly,Hong (Tuttle language library, 1991)
Speak Chinese Today! is a complete course in modern spoken Chinese ( putonghua , sometimes referred to as Mandarin Chinese), suitable for classroom use of self-study. It is the quickest way for travelers and businesspeople to learn Chinese